2009
DOI: 10.1111/j.1651-2227.2009.01437.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of human milk and its association with vitamins A and E and fatty acid composition

Abstract: Aim:The antioxidant capacity of human milk reflects the presence and activity of multiple components, which prevent oxidative rancidity. The aim of this study was to use the Oxygen Radical Absorbance Capacity assay to assess human milk antioxidant capacity and find correlations with milk components.Methods:Milk samples collected from 60 breastfeeding women at 1 month postpartum were assayed for antioxidant capacity, vitamins E and A, and fatty acids. Potential statistical relationships of concentrations of vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 28 publications
6
49
3
2
Order By: Relevance
“…10 However, a study in Canada observed a positive correlation between vitamin E found in milk and multivitamin supplementation, as reported by survey participants. 36 Dimenstein et al, 29 when analyzing tocopherol in the milk of 30 adult women in Northeastern Brazil, observed that supplementation with a capsule containing synthetic vitamin E (49.4 mg dl-alpha-tocopherol) did not lead to an increase in the concentration of the vitamin in colostrum 24 hours after supplementation. According to the authors, this indicates that the passage of this vitamin is limited and raises the question of the validity of offering supplements containing vitamin E with racemic mixtures.…”
Section: Maternal Habitual Dietary Intake and Vitamin E Supplementationmentioning
confidence: 96%
“…10 However, a study in Canada observed a positive correlation between vitamin E found in milk and multivitamin supplementation, as reported by survey participants. 36 Dimenstein et al, 29 when analyzing tocopherol in the milk of 30 adult women in Northeastern Brazil, observed that supplementation with a capsule containing synthetic vitamin E (49.4 mg dl-alpha-tocopherol) did not lead to an increase in the concentration of the vitamin in colostrum 24 hours after supplementation. According to the authors, this indicates that the passage of this vitamin is limited and raises the question of the validity of offering supplements containing vitamin E with racemic mixtures.…”
Section: Maternal Habitual Dietary Intake and Vitamin E Supplementationmentioning
confidence: 96%
“…Pre-formed vitamin A concentrations in human milk in Western countries were traditionally considered to be between 450 and 600 µg RE/L (69-92 µg RE/100 kcal), whereas considerably lower values were reported in two recent studies in Europe: 80 µg RE/L (12 µg RE/100 kcal) (Tijerina-Saenz et al, 2009) and 85 µg RE/L (13 µg RE/100 kcal) (Szlagatys-Sidorkiewicz et al, 2012).…”
Section: Vitamin a Content Of Human Milkmentioning
confidence: 99%
“…This antioxidant capacity is attributed mostly to alpha-tocopherol concentration [47]. Vitamin-E concentration in colostrum and preterm human milk is two times higher than in mature term milk, with a mean concentration of 1.9 IU/100 kcal, and an E/PUFA ratio of 2.0 in the first week.…”
Section: Recommendations For Vitamin Ementioning
confidence: 96%